Effectiveness of Acceptance and Commitment Therapy on Anxiety in Hypertensive Patient - Tantri Widyarti Utami; Yunani Sri Astuti (Indonesian Journal of Global Health Research, 2020)
Hypertension is a major problem in public health both in developed and developing countries. Emotional reactions due to hypertension are grieving, fear/anxiety, anger, depression and guilt. Anxiety is an unpleasant emotional by fear and tense and unwanted physical symptoms. Acceptance and commitment therapy (ACT) teaches clients to approach fear and anxiety more fundamentally, deeper, and in different ways Objective to knowing the effect of acceptance and commitment therapy on anxiety in hypertensive patients. Quasi-experimental design with a control group"with ACT interventions. The data obtained from 124 hypertensive patients who were divided into intervention and control groups. It analyzed by using Independent t-test and T-Paired tests. Research found there are differences in anxiety before and after intervention Acceptance and commitment therapy. Acceptance and commitment therapy can reduce the anxiety of hypertensive patients Keywords: acceptance and commitment therapy, anxiety, hypertension